2017
DOI: 10.1128/aac.00775-17
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Single-Dose Intravenous (ZTI-01) and Oral Fosfomycin in Healthy Volunteers

Abstract: The pharmacokinetics, safety, and tolerability of intravenous (i.v.) fosfomycin disodium (ZTI-01) and oral fosfomycin tromethamine were evaluated after a single dose in 28 healthy adult subjects. Subjects received a single 1-h i.v. infusion of 1 g and 8 g fosfomycin disodium and a single dose of 3 g oral fosfomycin tromethamine in a phase I, randomized, open-label, three-period crossover study. Serial blood and urine samples were collected before and up to 48 h after dosing. The mean pharmacokinetic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 32 publications
7
38
2
1
Order By: Relevance
“…8 A review of the FDA Adverse Events Reporting System for fosfomycin also noted similar aminotransferase level elevation rates (1-2%). 108 Other events noted in a phase I open-label trial of an IV fosfomycin 8-g dose were bradycardia (28.6%), defined as heart rate of 54 beats/minute or lower and hypocalcemia (10.7%) 43 These treatment-related adverse events resolved by the end of the study with the exception of one case of mild hypocalcemia and one case of anemia. No other laboratory abnormalities were observed in this study.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…8 A review of the FDA Adverse Events Reporting System for fosfomycin also noted similar aminotransferase level elevation rates (1-2%). 108 Other events noted in a phase I open-label trial of an IV fosfomycin 8-g dose were bradycardia (28.6%), defined as heart rate of 54 beats/minute or lower and hypocalcemia (10.7%) 43 These treatment-related adverse events resolved by the end of the study with the exception of one case of mild hypocalcemia and one case of anemia. No other laboratory abnormalities were observed in this study.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Intravenous fosfomycin pharmacokinetics (PK) has been studied in various phase I and II trials over the last several decades . More recent evaluations of IV fosfomycin 1‐ and 8‐g doses were performed in a phase I trial of 27 healthy adults (Table ) . The average age of subjects was 27 years, 40% were male, and mean creatinine clearance (Cl cr ) was 140 ml/minute.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current era of increasing prevalence of antibiotic resistance, fosfomycin has attracted renewed interest for the treatment of infections caused by multidrug-resistant pathogens, and especially UTIs. Indeed, it has a broad-spectrum antimicrobial activity and a favorable safety profile (4, 5). Fosfomycin-tromethamine, a soluble salt with improved bioavailability over fosfomycin, is currently recommended in single-dose as the first-line drug for the treatment of uncomplicated lower UTIs in Europe (6) and in the United States (7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Martin-Gutierrez et al recently demonstrated that anaerobiosis and acidic pH values in urine decreased fosfomycin MICs in strains harboring chromosomal resistance mutations (12). Finally, it has been previously shown that high concentrations (1000-4000 μg/ml) were achieved in urine after oral administration of 3 g of fosfomycin-tromethamine in humans and remained above 100 μg/ml for at least 30-40h (13), but data on concentrations in kidneys are scarce.…”
Section: Introductionmentioning
confidence: 99%